Pollutionary effect of the Medical city waste water on the Tigris river bacterial indicators on Baghdad city - Maalah, Warqa’a; ALAzzawi, Muhammed (Iraqi Journal of Science, 2023)
Bacteriological characteristics of Tigris river water were assessed monthly to monitor the impact of pollutants of Medical City waste water for the period from January to June-2013. Four stations were selected for the study, the first station placed before the Medical City Complex (500 meters). The second station represent Medical City sewage discharge into the river, where represents the study area. The third station placed (500 meters) after the second station, and the forth station is located on (2000 meters) after the second station.Samples collected monthly to monitor the changes of water indicators showed that: Total Bacterial Count (10000 to 2700000 cells/1 ml), Total Coliform (200-3700 cells/100 ml), Fecal Coliform (100-2400 cell/100 ml), Total Streptococci (200-2800 cells/100 ml), Fecal Streptococci (0-2000 cells/100 ml) and the FC: FS ratio is (0-8).